Covid-19 risk factors and health protocol compliance among mall employees and officers in Yogyakarta - Yunita Kemala Dewi; Ari Probandari (Fakultas Kedokteran Universitas Gadjah Mada, 2021)
Purpose: This study aimed to analyze risk factors, compliance with health protocols, and the COVID-19 screening test among mall employees at Yogyakarta city, Indonesia.Methods: We analyzed secondary data from a cross-sectional study in Yogyakarta City from May-August 2020. The population was all employees at all malls in Yogyakarta City who participated in the screening rapid test zero survey conducted by the Yogyakarta City Government. Results: Bivariate analysis showed a significant relationship between ensuring proper mask install (OR = 6.33, p = 0.023, 95% CI = 1.03-38.81), applying a minimum distance of > 1 meter when outside home (OR = 27.34, p = 0.001, 95% CI = 3.01-248.32) and applying a minimum distance of > 1 meter when at work (OR = 22.25, p = 0.003, 95% CI = 2,45-201.65) with the reactive COVID-19 results. Multivariate analysis showed the most dominant variable associated with the reactive rapid test results is not keeping a minimum distance of > 1 meter when outside the house with a value of (OR=11.91, p=0.047, 95% CI = 1.03-137.37). Conclusion: The risk factor for Covid-19 for employees and mall staff is physical distancing > 1 meter when outside the house. The city administration should keep working with mall managers to tighten health protocols in malls and other public areas to prevent Covid-19 transmission.